The association between, depression, anxiety, and mortality in older people across eight low‐ and middle‐income countries: Results from the 10/66 cohort study. (24th October 2019) - Wu, Yu‐Tzu; Kralj, Carolina; Acosta, Daisy; Guerra, Mariella; Huang, Yueqin; Jotheeswaran, Amuthavalli T.; Jimenez‐Velazquez, Ivonne Z.; Liu, Zhaorui; Llibre Rodriguez, Juan J.; Salas, Aquiles; Sosa, Ana Luisa; Alkholy, Rasha; et al.
Abstract : Objectives: Depression and anxiety are common mental disorders in later life. Few population‐based studies have investigated their potential impacts on mortality in low‐ and middle‐income countries (LMICs). The aim of this study is to examine the associations between depression, anxiety, their comorbidity, and mortality in later life using a population‐based cohort study across eight LMICs. Methods: This analysis was based on the 10/66 cohort study including 15 991 people aged 65 years or above in Cuba, Dominican Republic, Venezuela, Mexico, Peru, Puerto Rico, China, and India, with an average follow‐up time of 3.9 years. Subthreshold and clinical levels of depression were determined using EURO‐D and ICD‐10 criteria, and anxiety was based on Geriatric Mental State (GMS)–Automated Geriatric Examination for Computer Assisted Taxonomy (AGECAT). Cox proportional hazard modelling was used to estimate how having depression, anxiety, or both was associated with mortality adjusting for sociodemographic and health factors. Results: Participants with clinical depression (hazard ratio [HR]: 1.45; 95% CI, 1.24‐1.70) and subthreshold anxiety (HR: 1.26; 95% CI, 1.15‐1.38) had higher risk of mortality than those without the conditions after adjusting for sociodemographic factors and health conditions. Comorbidity of depression and anxiety was associated with a 30% increased risk of mortality but the effect sizes varied across countries (Higgins I 2  = 58.8%), with the strongest association in India (HR: 1.99; 95% CI, 1.21‐3.27). Conclusions: Depression and anxiety appear to be associated with mortality in older people living in LMICs. Variation in effect sizes may indicate different barriers to health service access across countries. Future studies may investigate underlying mechanisms and identify potential interventions to reduce the impact of common mental disorders.